Glocalizing Integrated STEM: Policy Translation and Teacher Perspectives in Urban West Jakarta - Yurika Oktaviane; Suryanti Suryanti; Neni Mariana; Ganes Gunansyah (Pedagogy Review, 2026)
This study describes the translation of global policies on integrated STEM into local classroom practices by elementary school teachers in West Jakarta through a glocalization lens. It fills a gap in the literature on non-Western urban contexts where environmental challenges such as flooding shape everyday teaching. A sequential explanatory mixed-methods design was utilized. In the quantitative phase, 94 teachers from six districts completed a 39-item survey that measured STEM knowledge, self-efficacy, barriers, and local relevance. Stratified random sampling was used to ensure district representation. In the qualitative phase, 12 teachers were purposively selected, and semi-structured interviews were conducted and analyzed with reflexive thematic analysis based on glocalization theory. The results show a paradox: teachers strongly believe in the importance of STEM in elementary education (M = 4.68). However, they are not confident in designing integrated lessons (M = 3.42) and applying engineering design (M = 3.38). Teachers in flood-prone districts (Cengkareng and Kalideres) gave higher marks to the community relevance of STEM than teachers in more developed areas, demonstrating how contextual adaptation is driven by local environmental challenges. Qualitative analysis revealed teachers’ active glocalization through the integration of local flooding, waste management, traditional markets, and community recycling into STEM lessons. Collaborative Networks Build Confidence: Teachers who worked with peers regularly (weekly or biweekly) expressed greater self-efficacy and persistence. Curriculum constraints (M = 4.21) and limited preparation time (M = 4.18) were the main barriers. The study concludes that three systemic interventions are needed for sustainable STEM integration. These include reforming pre-service curricula to include interdisciplinary STEM design, allocating infrastructure grants to resource-constrained, flood-prone districts, and replacing one-shot workshops with sustained school-based coaching and professional learning communities. Meaningful reform must place teachers as active agents of glocalization. Keywords: elementary school, glocalization, integrated STEM education, policy translation, teacher perspectives.